Development of Chromatin Immunoprecipitation (ChIP) For Analysis of Chromatin Modifications at a Gene Silenced by Toxoplasma gondii Infection in Neuronal Cells. - Norhidayah, Badya; McConkey, Glenn (2018)
Neuroepigenetic regulation has been shown to be important for key processes in the brain from learning and memory to behaviour and neurodegenerative diseases. Chromatin modifications can be modulated by environmental factors. We are investigating chromatin modifications induced in neurones by infection with Toxoplasma gondii where our laboratory has observed transcriptional gene silencing (TGS). For this, we are developing a Chromatin Immunoprecipitation (ChIP) protocol to analyse these chromatin modifications.